Rationale and design of Diabetes Prevention with active Vitamin D (DPVD): a randomised, double-blind, placebo-controlled study - Yoshiya Tanaka; Yosuke Okada; Tetsuya Kawahara; Gen Suzuki; Tetsuya Inazu; Shoichi Mizuno; Fumiyoshi Kasagi (BMJ Open)
Introduction Recent research suggests that vitamin D deficiency may cause both bone diseases and a range of non-skeletal diseases. However, most of these data come from observational studies, and clinical trial data on the effects of vitamin D supplementation on individuals with pre-diabetes are scarce and inconsistent. The aim of the Diabetes Prevention with active Vitamin D (DPVD) study is to assess the effect of eldecalcitol, active vitamin D analogue, on the incidence of type 2 diabetes among individuals with pre-diabetes.Methods and analysis DPVD is an ongoing, prospective, multicentre, randomised, double-blind and placebo-controlled outcome study in individuals with impaired glucose tolerance. Participants, men and women aged ≥30 years, will be randomised to receive eldecalcitol or placebo. They will also be given a brief (5–10 min long) talk about appropriate calorie intake from diet and exercise at each 12-week visit. The primary end point is the cumulative incidence of type 2 diabetes. Secondary endpoint is the number of participants who achieve normoglycaemia at 48, 96 and 144 weeks. Follow-up is estimated to span 144 weeks.Ethics and dissemination All protocols and an informed consent form comply with the Ethics Guideline for Clinical Research (Japan Ministry of Health, Labour and Welfare). The study protocol has been approved by the Institutional Review Board at Kokura Medical Association and University of Occupational and Environmental Health. The study will be implemented in line with the CONSORT statement.Trial registration number UMIN000010758; Pre-results.